Comparative evaluation of scenario-based clinical examinations in orthodontic certification: Insights from Taiwan and the United States - Chia Tze Kao; Tzu Ying Wu; Chun Liang Kuo; Chung-Hsing Li; Chen-Feng Cheng; Yu-Kun Chih (Journal of Dental Sciences, 2025)
Background/purpose: The scenario-based clinical examination (SBCE) is a structured assessment used in orthodontic certification to evaluate candidates’ clinical reasoning, decision-making, and problem-solving abilities. This study compared the implementation of SBCE in Taiwan (Taiwan Board of Orthodontics, TBO) and the United States (American Board of Orthodontics, ABO) to determine whether their examination structures aligned with clinical practice demands. Materials and methods: The TBO and ABO certification processes were analyzed based on their examination structure, scoring criteria, and pass rate trends from 2019 to 2024. Both organizations incorporated a written examination and an SBCE, but TBO required additional self-completed case submissions, whereas ABO did not. The TBO SBCE process included examiner training, collaborative question development, and structured scoring criteria based on predefined competency benchmarks. Results: TBO pass rates remained stable between 75 and 87.8 % after implementing SBCE, whereas ABO pass rates showed greater variation (64–91 %), potentially due to COVID-19 disruptions. The structured TBO SBCE process ensured fairness, transparency, and standardization, maintaining stable examination outcomes. Conclusion: SBCE has proven to be a reliable and objective method for orthodontic certification. By implementing a criterion-referenced scoring system, TBO ensures that its examination aligns with professional standards. The study suggests that SBCE enhances orthodontic competency assessment and should be considered for broader adoption in certification programs worldwide.